Total testosterone in young men is more closely associated than free testosterone with prostate cancer disparities - Alvarado, Louis Calistro (SAGE Publications, 2011)
Introduction: Early adulthood has been suggested as the most relevant time to determine the influence of testosterone on prostate carcinogenesis. For a more detailed assessment of this hypothesis, the present study examined whether serum total or free testosterone in young men was more closely associated with prostate cancer disparities. Methods: A literature search was conducted for studies that reported both total and free testosterone levels for population samples of young men, along with prostate cancer incidences for the populations from which study populations were sampled. A previously developed analytical method was used to standardize the hormone levels of 19 population samples gathered from nine studies, and these standardized values were compared with disparities in prostate cancer incidence. Results: Population differences in total testosterone levels were significantly associated with prostate cancer disparities, r = 0.833, p = 0.001, as were population differences in free testosterone, r = 0.661, p = 0.027. After controlling for age differences, total and free testosterone remained associated with prostate cancer disparities, partial r = 0.888, p < 0.001, and partial r = 0.657, p = 0.039, respectively. A marginally significant difference existed in the strength of relationships between total and free testosterone with respect to prostate cancer disparities, with total testosterone exhibiting a stronger association, T(2) = 1.573, p = 0.077. Conclusions: Across analyses, total testosterone demonstrated a more robust relationship than free testosterone with cancer disparities, which may suggest that total testosterone is the more sensitive biomarker for evaluating androgenic stimulation of the prostate gland.